'Ainulmardiyyah: A Heavenly Reward Promised by Acehnese Jihad Texts (Malay Literature, 2023)
The sanctity of Acehnese conceptualisation of jihad for the promise of heaven becomes apparent via a heavenly houri called 'Ainulmardiyyah. She is the maiden waiting for her "husbands" in the heaven who fall in the battlefield. This paper discusses the portrayal of ʻAinulmardiyyah (maidens in heaven for a Muslim martyr) in the most celebrated Acehnese text on Islamic holy war, Hikayat Prang Sabi (HPS). The hikayat text is first approached philologically to verify the adaptations that likely have been made. Methods of commentary are employed by comparing the portrayal of the houri in the hikayat and other texts with holy war themes. The texts are then approached semantically to analyse any underlying concepts and standard vocabularies used in text on the female charm. Hence, this guides this paper to formulate a pattern of how portrayal of the houri is used to spur the mujahidin to fight for the dignity of their religion and state. It is found that the endorsement of 'Ainulmardiyyah in the Hikayat Prang Sabi text is subject to Islamic teaching that is transmitted not only through the Qur'an and the sunnah, but also numerous Islamic eschatological texts heralding the holiness of martyrdom in jihad. The promise of the tantalising reward of heaven is also intensified by socio-political factors throughout Aceh's history.Full text: PDF